ANALISIS PENGARUH KUALITAS PRODUK, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DAN CITRA MEREK SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN IMAGINE SIGNATURE DIBIDANG JASA INTERIOR - julius; Subagiyo; Noviarti (Pasca Sarjana Universitas Satya Negara Indonesia, 2024)
This study aims to analyze the influence of product quality, price and promotion on purchasing decisions partially or simultaneously. Analyzing the effect of product quality, price, promotion and brand image on purchasing decisions and analyzing the mediating effect of brand image on the influence of product quality, price and promotion on purchasing decisions. The method used in this research is the descriptive quantitative method. This research was conducted at the company Imagine Signature in the field of interior design services with 40 respondents, namely customers. The data collection method is in the form of a questionnaire with a Likert scale which is tested for validity and reliability. The analysis method used in this research is the path analysis method with linear regression and classic assumptions. The results of this research indicate that product quality, price and promotion have a positive and significant effect on brand image both partially and simultaneously. In addition, product quality, price, promotion and brand image have a positive and significant influence on purchasing decisions. The brand image variable has proven unable to mediate the influence of product quality, price and promotion on purchasing decisions at the imagine signature company in the field of interior design services.